Uncertainty models for stochastic optimization in renewable energy applications - Zakaria A.; Ismail F.B.; Lipu M.S.H.; Hannan M.A. (Elsevier Ltd, 2023)
Decision making; Optimization; Renewable energy resources; Stochastic systems; Uncertainty analysis; Deterministic optimization method; Renewable energy applications; Renewable energy integrations; Renewable energy systems; Scenario generation; Stochastic optimization methods; Stochastic optimizations; Uncertainty modeling; Stochastic models; alternative energy; integrated approach; model; optimization; power generation; sampling; stochasticity